Effect of additional types of different probiotics on feed on the consumption rate, feed conversion ratio, protein, and fat retention Cyprinus carpio: Effect of additional types of different probiotics on feed on the consumption rate, feed conversion ratio, protein, and fat retention Cyprinus carpio - Linda Puspitasari; Woro Hastuti Satyantini; Arif Habib Fasya (Universitas Muhammadiyah Malang, 2022)
Cyprinus carpio is a freshwater fish that is in great demand by the public because of several advantages, including its high protein content and affordable price. Carp (C. carpio) cultivation requires artificial feed as nutrients to support its growth. One aspect of stunted growth is low feed utilization, this is related to feed protein digestibility that is not optimal. One way to increase the digestibility of feed is by adding probiotics. The purpose of this study was to examine the addition of probiotics to artificial feed on the level of feed consumption, the value of the feed conversion ratio, the retention of protein in meat and retention of fat in the fish of Cyprinus carpio. This research was conducted in May-June 2022 at the Laboratory of the School of Health and Natural Sciences. The results found that the addition of different types of probiotics to the feed can affect the level of consumption, feed conversion ratio, protein retention and fat retention of Cyprinus carpio fish. This study used an experimental method with a completely randomized design with 5 treatments and 4 replications. Observations on each treatment showed different results. The results showed that probiotics had an effect (p<0.05) on TKP, RKP, RP, and RL. The best use of probiotics is found in P4 with the content of probiotic bacteria, namely Lactobacillus sp. Acetobacter sp. and yeast. The results obtained in the P4 treatment with a total value of 105.93 grams of feed consumption, 1.40 feed conversion ratio value, 65.68% meat protein retention value, and 187.59% meat fat retention value